2021
DOI: 10.3389/fphar.2021.654699
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Formulation Secret Underlying Chinese Huo-Clearing Herbal Drink

Abstract: Herbal teas or herbal drinks are traditional beverages that are prevalent in many cultures around the world. In Traditional Chinese Medicine, an herbal drink infused with different types of medicinal plants is believed to reduce the ‘Shang Huo’, or excessive body heat, a status of sub-optimal health. Although it is widely accepted and has a very large market, the underlying science for herbal drinks remains elusive. By studying a group of herbs for drinks, including ‘Gan’ (Glycyrrhiza uralensis Fisch. Ex DC.),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…However, this principle is difficult to follow in practice, due to the multiple symptoms of diseases and polyfunctionality of medicinal plants. Therefore, many formulas of TCM contain secrets that are not always explained by rationality ( Wang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, this principle is difficult to follow in practice, due to the multiple symptoms of diseases and polyfunctionality of medicinal plants. Therefore, many formulas of TCM contain secrets that are not always explained by rationality ( Wang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in vitro studies have indicated that licorice was effective in combination with other herbs could decrease a few classical cytokines including TNF-α, IL-1β, MCP-1, and IFN. The levels of cytokines were back to normal, indicating that licorice composed with other herbs helps reduce the inflammatory level (Wang et al, 2021).…”
Section: Anti-inflammatory Effectsmentioning
confidence: 98%
“…Beyond that, E channel was also found to participate in MERS-CoV assembling, virion release, and pathogenesis. Thus, the small molecules targeting SARS-CoV2 envelope protein could also be potential broad-spectrum anticoronavirus drugs, such as an inhibitor of E protein (Tomar et al, 2021;Wang et al, 2021). In summary, licorice may directly or indirectly protect target organs by inhibiting the binding of the virus to ACE2, antioxidant, and anti-fibrosis effects (Ming et al, 2020).…”
Section: Ace2 Inhibitionmentioning
confidence: 99%
“…Preliminary studies demonstrated the in-vivo and in-vitro anti-inflammatory activity of aqueous extracts of Ju. However, Ju alone caused obvious weight loss of the mice and it could be recovered by additional Gan extract ( Wang et al, 2021 ). Previously, we established an inflammatory endothelial cell model to screen and quantify a variety of anti-inflammatory Chinese herbal medicines ( Zhang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we established an inflammatory endothelial cell model to screen and quantify a variety of anti-inflammatory Chinese herbal medicines ( Zhang et al, 2018 ). Using this novel cell model, we found that Ju and Jin in association with Gan provided better anti-inflammatory effects along with increased immunity of the body ( Wang et al, 2021 ). As inflammation and tumorigenesis are closely related ( Weiss, 2008 ; Singh et al, 2019 ), we therefore examined the combined effects of anti-inflammatory and antitumor Chinese herbal formulations in both in vitro and in vivo conditions in the presence of tumor chemotherapy.…”
Section: Introductionmentioning
confidence: 99%